Efforts to Increase Student Interest in Classical Al-Qur'an and Hadith Learning through Educational Games at Mts Nurul Huda - Sa'diah, Kalimatus; Saruksuk, Jumiadi (MANDAILING GLOBAL EDUKASIA, 2024)
Education that only implements administrative and instructional fields by ignoring Al-Qur'an Hadith lessons will only produce students who are smart and skilled in academic aspects, but lack maturity in personality aspects. The approach in Al-Qur'an Hadith lesson services is now more comprehensive, meaning that Al-Qur'an Hadith lesson services are based on efforts to achieve developmental tasks, develop potential, and overcome student problems. One of the efforts to help achieve developmental tasks carried out by Al-Qur'an Hadith lessons is content mastery. Content mastery is mastery of content that helps students (clients) master certain content, especially competencies and/or habits that are useful in life at school, family and society. The results of observations in the field where the researcher was on duty found that many MTs Nurul Huda students in implementing the mastery of classical Al-Qur'an Hadith lesson content were often less interested due to the monotonous and less varied presentation. In following the Mastery of the Content of classical Al Qur'an Hadith lessons, it is necessary to find alternative methods that can enchant students' interests, by providing educational games it is hoped that the service activity process can run smoothly, be fun, and students unconsciously learn from their experiences to reflect on the learning activities they do happily. Educational games used in the content mastery service of classical Al Qur'an Hadith guidance here include: Interactive Quiz Game (Quizizz/Kahoot) Verse Puzzle (Arrange the Verses) Guess the Murottal Picture Looking for the Missing Hadith Who Am I? (Guess the Character in the Hadith) Matching Game (Verse Pairs & Translations) Ranking 1 (Classical Competition) Story Telling Verses and Hadith. The research was conducted in 2 cycles, with the following results: (1) Students felt happy with the game in mastering classical Al-Quran Hadith content because it could help create a warm, friendly and pleasant atmosphere during the teaching and learning process, thus helping to facilitate the process of mastering the expected content. (2) Students had an understanding of the goals and benefits of the game in mastering the content. (3) Students had the enthusiasm and ability to realize the attitudes reflected through the game in classical Al-Quran Hadith lessons in real performance such as not lying, being patient, disciplined, concentrating, diligently attending school, focusing and cooperating.